2017
DOI: 10.1208/s12249-017-0795-0
|View full text |Cite
|
Sign up to set email alerts
|

Development of Cordycepin Formulations for Preclinical and Clinical Studies

Abstract: There is extensive literature on in vivo studies with cordycepin, but these studies were generally conducted without validation of the various formulations, especially in terms of the solubility of cordycepin in the dosing vehicles used. Cordycepin is a promising drug candidate in multiple therapeutic areas, and there is a growing interest in studies aimed at assessing the pharmacological activity of this compound in relevant animal disease models. It is likely that many reported in vivo studies used formulati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 36 publications
1
17
1
Order By: Relevance
“…Control group included those having sham surgery, in which the ligament was visualised but not transected. From week 14 to 16 mice were orally gavaged every other day with 200 µl cordycepin (8 mg/kg) or vehicle (23% propylene glycol [PPG] in distilled water) 34 . Pain behaviour was measured once weekly following model induction and then twice weekly following cordycepin treatment, until week 16.…”
Section: Methodsmentioning
confidence: 99%
“…Control group included those having sham surgery, in which the ligament was visualised but not transected. From week 14 to 16 mice were orally gavaged every other day with 200 µl cordycepin (8 mg/kg) or vehicle (23% propylene glycol [PPG] in distilled water) 34 . Pain behaviour was measured once weekly following model induction and then twice weekly following cordycepin treatment, until week 16.…”
Section: Methodsmentioning
confidence: 99%
“…Prior to pharmacokinetic studies, jugular vein cannulation surgery was performed under general anaesthesia (<3% isoflurane inhalation) for blood sampling or intravenous drug administration. Following two nights of recovery from surgery, the animals were intravenously or orally administered with the PBS-based formulation (5.5 mg/mL cordycepin) developed in a previously reported study 22 . The dose was 8 or 20 mg/kg for intravenous administration and 8 or 80 mg/kg for oral administration.…”
Section: Methodsmentioning
confidence: 99%
“…Cordycepin has been reported to have a diverse range of pharmacological effects of which the most well-studied areas include anti-inflammation, anti-proliferation and pro-apoptosis 1921 . The wide range of potential therapeutic applications of cordycepin has drawn substantial research interest in the compound which resulted in numerous preclinical in vivo efficacy studies in different species 22 . Reports include claims of efficacy in animal models of bone loss 23 , vascular disorder 24 , cognitive dysfunction 25 , sleep disorders 26 , cancer 21,27 , neuronal degeneration 28 , hyperlipidaemia 29 , oxidative stress 30 , hyperglycaemia 31 , asthma and lung inflammation 32 and viral infection 33 .…”
Section: Introductionmentioning
confidence: 99%
“…Previous work demonstrated that phosphate-buffered saline (PBS, pH 4.0) is a suitable solvent for COR in intravenous and oral treatments at low doses. Propylene glycol (PPG) is more applicable than PBS at pH 4.0 as a COR solvent for oral treatments [136]. Complex mechanisms of action: COR inhibits and/or induces multiple medicinal targets in a dose-dependent, condition-dependent and nonspecific manner: Different concentrations of COR exhibit diverse effects on MA-10 mouse Leydig tumor cells (MLTCs).…”
Section: Pros and Cons Of Cor In Clinical Applicationsmentioning
confidence: 99%
“…Previous work demonstrated that phosphate-buffered saline (PBS, pH 4.0) is a suitable solvent for COR in intravenous and oral treatments at low doses. Propylene glycol (PPG) is more applicable than PBS at pH 4.0 as a COR solvent for oral treatments [136].…”
Section: Pros and Cons Of Cor In Clinical Applicationsmentioning
confidence: 99%